Estate appraisal as an example of social network analysis (SNA) - Taktak, Fatih; Demir, Hulya (ACADEMIC JOURNALS, 2011)
In the transition to an information society, a government structure that possesses integrated, efficient, transparent and simplified business processes is a basic principle. In line with this, providing interoperability within the public sector that encompasses not only corporations and organizations but also local administrations and identifying the necessary procedures and standards for this is of significant importance. In this context, the social network analysis (SNA) is an effective tool. Using SNA, this study examined real estate (immovable) appraisal (valuation) that is widely used by the public sector as well as the private sector that is realized through multi-headed organizational structures in Turkey. With the numerical and visual analysis conducted at the central county of the province of Afyonkarahisar, answers were sought to questions such as, In the work relating to real estate appraisal which organization is most concerned? In obtaining real estate appraisal related data which organization is cooperated with the most? Of the organizations that undertake real estate appraisal which organization is known the most? Which organization that carries out real estate appraisal is trusted the most? In conclusion, the relationship between organizations that undertook real estate appraisals were evaluated using the SNA and an unseeable social relationship network was revealed.
Keywords: Social networks; social network analysis; real estate appraisal; Turkey; INTEROPERABILITY; Business & Economics